2016
DOI: 10.1108/jpbm-03-2015-0834
|View full text |Cite
|
Sign up to set email alerts
|

Brand love and positive word of mouth: the moderating effects of experience and price

Abstract: Purpose This study aims to test and extend Carroll and Ahuvia’s (2006) model on the antecedents and outcomes of brand love by examining the moderating effects of experience and price on the relationship between brand love and offline word of mouth (WOM) and between brand love and electronic WOM (eWOM). Design/methodology/approach An online survey was conducted on Facebook, which generated 342 valid responses. The data were analyzed using partial least squares-structural equation modeling. Findings The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
218
2
35

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 230 publications
(283 citation statements)
references
References 80 publications
8
218
2
35
Order By: Relevance
“…Despite the fact that there are some exceptions, such as the proposal of specific personalized items that present a maximum premium price to be recommended (Moon et al, ), it is generally accepted the influence of price premium on WOM as it was confirmed in this study. This relationship will be different depending on the product category or country's risk (Karjaluoto et al, ). Finally, the effect of loyalty on WOM was validated in line with other authors that propose this relationship from a theoretical perspective (Dick & Basu, ); quantify this effect in sales (Kim et al, ); or even prove a direct and indirect influence through satisfaction (Casidy & Wymer, , ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the fact that there are some exceptions, such as the proposal of specific personalized items that present a maximum premium price to be recommended (Moon et al, ), it is generally accepted the influence of price premium on WOM as it was confirmed in this study. This relationship will be different depending on the product category or country's risk (Karjaluoto et al, ). Finally, the effect of loyalty on WOM was validated in line with other authors that propose this relationship from a theoretical perspective (Dick & Basu, ); quantify this effect in sales (Kim et al, ); or even prove a direct and indirect influence through satisfaction (Casidy & Wymer, , ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between price premium and WOM will be stronger in countries with less risk and will be different depending on the product category. Price also mediates between a brand, and WOM strengthens this relationship mainly in the offline recommendations (Karjaluoto et al, ). In the food context, a recent study by Hanaysha () outlines how the increment of prices can affect the recommendations to others.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…As fans retort largely to new relevant content, which support posts placed in the late afternoon. Here the outcomes contour in the midst of data concerning the practice of the social media facebook dais, illustrates so as to majority fans and followers approach in facebook in morning or afternoon (Karjaluoto, Karjaluoto et al, 2016). The control variable "geography" has an optimistic significance on participation, through a top scale for the valley and Centre, where several of the most active TMs (Tafesse and Tafesse, 2016) are located.…”
Section: Empirical Analysismentioning
confidence: 99%